2019
DOI: 10.26504/bkmnext376
|View full text |Cite
|
Sign up to set email alerts
|

Diverse neighbourhoods: an analysis of the residential distribution of immigrants in Ireland

Abstract: Diverse communities are an integral part of Irish life, with almost 12 per cent of people living here having a nationality other than Irish, and a growing second and third generation of Irish-born children of migrants. Where migrants live is key to their social inclusion: the neighbourhoods they call home. Ireland's National Migrant Integration Strategy is one way in which we are trying to remove barriers to fully realising the potential and opportunities that diversity can bring. The Strategy is underpinned b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…In the summer, most areas had a prevalence of deficiency of less than 10% except locations such as north and west Dublin including Lucan. This may be in part accounted for by a greater proportion of individuals of Asian and Black ethnicity living here [47]. Indeed, those with darker or more pigmented skin have a greater risk of deficiency at locations in northern latitudes [26].…”
Section: Vitamin D Status By Season and Locationmentioning
confidence: 98%
“…In the summer, most areas had a prevalence of deficiency of less than 10% except locations such as north and west Dublin including Lucan. This may be in part accounted for by a greater proportion of individuals of Asian and Black ethnicity living here [47]. Indeed, those with darker or more pigmented skin have a greater risk of deficiency at locations in northern latitudes [26].…”
Section: Vitamin D Status By Season and Locationmentioning
confidence: 98%
“…a more detailed occupational breakdown might reduce the EU-East* Q2 interaction. Geographical location may also interact with sector; we know that migrants are more residentially concentrated within cities (Fahey et al, 2019) and larger cities may be more prone to COVID-related unemployment in the service sector.…”
Section: Figure 44 Predicted Probability Of Employment In Q1 and Q2 mentioning
confidence: 99%
“…Authors' calculations. Labour Force Survey (Q1-Q4, 2017-2019.Notes:Includes all employees aged 15 or over.Figure listsproportions and 95 per cent confidence intervals by group. Data for North America, Australia and Oceania (NAO) and Africa are unavailable due to small cell sizes.…”
mentioning
confidence: 99%
“…Recent research using Census 2016 microdata has shown that immigrants in Ireland with better self-rated English language skills are more likely to be employed and have better jobs when they are employed (McGinnity et al, 2020). Fahey et al (2019), analysing the residential distribution of immigrants in Ireland, find that while there is no evidence that migrants in general are concentrated in disadvantaged areas in Ireland. However, migrants with poor English language skills do tend to live in areas of higher unemployment, particularly in the urban areas of Dublin, Cork and Limerick, suggesting that this group may be disadvantaged relative to others.…”
Section: Language Requirementsmentioning
confidence: 99%